2023
DOI: 10.1155/2023/1496597
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of Motor Neurons and Purkinje Cells Differentiated from Induced Pluripotent Stem Cells Generated from Patients with Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay

Abstract: Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is an early-onset neurodegenerative disease mainly characterized by spasticity in the lower limbs and poor muscle control. The disease is caused by mutations in the SACS gene leading in most cases to a loss of function of the sacsin protein, which is highly expressed in motor neurons and Purkinje cells. To investigate the impact of the mutated sacsin protein in these cells in vitro, induced pluripotent stem cell- (iPSC-) derived motor neurons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Cytoskeleton components are yet known to have an important role in ARSACS pathogenesis ( Duncan et al, 2017 ; Louit et al, 2023 ), but microfilaments structure and dynamics have never been reported in ARSACS models. Our analysis indicated an aberrant expression of actin and actin-binding proteins, unraveling a potential role of actin cytoskeleton in the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoskeleton components are yet known to have an important role in ARSACS pathogenesis ( Duncan et al, 2017 ; Louit et al, 2023 ), but microfilaments structure and dynamics have never been reported in ARSACS models. Our analysis indicated an aberrant expression of actin and actin-binding proteins, unraveling a potential role of actin cytoskeleton in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…ARSACS is caused by mutations in SACS ( Engert et al, 2000 ), a gene encoding sacsin whose “scaffold- like” and multidomain organization suggests involvement in protein quality control ( Romano et al, 2013 ). Recent findings point to loss-of-function mechanism in ARSACS ( Longo et al, 2021 ), and multiple in vitro and in vivo studies suggest that sacsin plays roles in mitochondrial dynamics ( Girard et al, 2012 ; Criscuolo et al, 2015 ), cytoskeletal filament assembly and dynamics ( Duncan et al, 2017 ; Louit et al, 2023 ), axonal development ( Ady et al, 2018 ; Romano et al, 2022 ), and Ca 2+ homeostasis ( Del Bondio et al, 2023 ). Yet, the question of how mutant sacsin leads to disease status in patients with ARSACS remains to be answered.…”
Section: Introductionmentioning
confidence: 99%